Kış Turizmi Potansiyeli Açısından Muş İlinin SWOT Analizi İle Değerlendirilmesi - Arslan, Emin; Kendir, Hakan (Muş Alparslan Üniversitesi, 2019)
It isobserved that there is a significant potential for winter tourism especially inthe provinces of Eastern Anatolia Region in Turkey, but investments areconcentrated in certain centers. With the completion of past terrorist eventsin the past years, it is possible for the Eastern Anatolia Region to attractmore investment for winter tourism. However, Muş province is not yet at thedesired point in terms of winter tourism investment. In the scope of thisstudy, it is aimed to evaluate the potential of winter tourism and to revealthe possibilities of winter tourism in the province of Muş where winter seasonis quite harsh and there are facilities for winter tourism (such as GüzeltepeSki Center). SWOT method was used in this scope of study. With this research, it is aimed that to be realized by the decision makers that the province of Muşcan be reached as a winter tourism destination.

Türkiye’ninDoğu Anadolu Bölgesi’nde yer alan illerde, kış turizmine yönelik önemli birpotansiyelin bulunduğu ancak belli merkezlerde yatırımların yoğunlaştığıgörülmektedir. Geçmişte var olan terör olaylarının son yıllarda bitirilmesiylebirlikte Doğu Anadolu Bölgesi’nin kış turizmine yönelik daha fazla yatırımçekmesi olasıdır. Ancak Muş ili kış turizmi yatırımı anlamında henüz istenilennoktada bulunmamaktadır. Bu çalışma kapsamında, kış mevsiminin oldukça sertgeçtiği ve kış turizmine yönelik (Güzeltepe Kayak Merkezi gibi) imkânlarınbulunduğu Muş ilinde, kış turizmi potansiyelinin değerlendirilmesi ve kışturizmi olanaklarının ortaya konması amaçlanmaktadır. Çalışma kapsamında GZTFanalizi yöntemi kullanılmıştır. Yapılan bu araştırma ile Muş ilinin bir kışturizmi destinasyonu olarak hak ettiği konuma ulaştırılabileceğinin kararvericiler tarafından fark edilmesi hedeflenmektedir.
The Evaluation With SWOT Analysis of the Muş Province in Terms of Winter Tourism Potential
anemon
Keywords: Muş; Tourism; Winter Tourism; Muş; Turizm; Kış Turizmi